Suprachoroidal Bleeding After XEN Gel Implantation. Issue 12 (December 2017) - Prokosch-Willing, Verena; Vossmerbaeumer, Urs; Hoffmann, Esther; Pfeiffer, Norbert
Abstract : Purpose: To report for the first time a clinical case of suprachoroidal bleeding after XEN45 gel implantation. Observations: A 84-year old female patient with pseudoexfoliation glaucoma with intraocular pressure (IOP) (20 mm Hg) above target despite maximal IOP-lowering therapy was scheduled for XEN45 gel implantation. The XEN45 gel implantation went without complications and was properly placed in the anterior chamber and beneath the conjunctiva. On the first postoperative day, the patient presented with an IOP of 4 mm Hg, a functioning bleb and a deep anterior chamber. On the second day she developed suprachoroidal bleeding. A wait and see strategy was followed and the patient monitored steadily. The bleeding resolved spontaneously after 6 weeks. Conclusions and Importance: Minimally invasive glaucoma surgery is developed to provide a safer and less-invasive option to reduce IOP in glaucoma patients compared with trabeculectomy. Although the concept of the XEN45 gel stent seems to be a favorable to reach IOP-lowering results similar to those of trabeculectomy, complications may be similar, too. We have to keep this in mind when informing patients about surgical options.